2006
DOI: 10.1111/j.1745-4603.2006.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Compression, Tension and Torsion for Testing Food Gel Fracture Properties*

Abstract: Three fracture test methods: uniaxial compression, uniaxial tension and torsion were examined by interpreting results using theories upon which the methods were based. In each of these tests, the fracture of gels can occur as a result of shear, compression or tension. The fracture properties determined from uniaxial compression and tension were compared with torsion testing, a suitable reference technique. Shear stress and strain in uniaxial compression were comparable with shear stress and strain in torsion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…For this reason a series of assumption were considered which were described in the following parts of this section. Regarding the high rate of moisture content in food materials, they are considered as incompressible materials (Gao et al 1993;Hamann et al 2006;Coburn and Pandit 2007;Miller et al 2007;Daubert and Foegeding 2010). Previous studies on apple and potato tissues under external source of load indicated an incompressible behaviour (Mitsuhashi-Gonzalez et al 1995, Scanlon andLong 1995).…”
Section: Theory and Calculationmentioning
confidence: 99%
“…For this reason a series of assumption were considered which were described in the following parts of this section. Regarding the high rate of moisture content in food materials, they are considered as incompressible materials (Gao et al 1993;Hamann et al 2006;Coburn and Pandit 2007;Miller et al 2007;Daubert and Foegeding 2010). Previous studies on apple and potato tissues under external source of load indicated an incompressible behaviour (Mitsuhashi-Gonzalez et al 1995, Scanlon andLong 1995).…”
Section: Theory and Calculationmentioning
confidence: 99%
“…Another important consideration is the geometric coupling of fracture stress and fracture strain. When the gel fracture criteria is a stress level, fracture strain is a function of elongation needed to reduce the specimen cross section to an area producing the critical fracture stress (Hamann et al, 2006). This results in similar increase or decrease of fracture stress and fracture strain with varying variables such as concentration.…”
Section: Uniaxial Tensionmentioning
confidence: 99%
“…A breaking angle of 45°results from shear stresses (Hamann et al, 2006). Therefore, only upright samples with a breaking angle of 45°after deformation were considered for calculation.…”
Section: Uniaxial Compression Testmentioning
confidence: 99%
“…A uniaxial compression test was used for low speeds because shear stresses, one of the main mechanical stresses on vegetables during processing, can be directly measured (Hamann, Zhang, Daubert, Foegeding, & Diehl, 2006). Furthermore, an impact test was used to test the vegetables at high speeds.…”
Section: Textural Analysismentioning
confidence: 99%